International production sharing: A case for a coherent policy framework - Hildegunn Kyvik Nordås (World Trade Organization (WTO), 2007)
This study seeks to clarify what vertical specialization/fragmented production/production sharing is, how widespread it is, how it is organized, its driving forces, and what the policy implications are. It presents six country case studies ( USA, Japan, Germany, Brazil, China and South Africa ) where the importance and nature of production sharing or vertical specialization in the automotive and electronics sectors are studied for each country. The automotive industry has always been a leading industry in terms of organizational innovations and recent developments in the sector raise interesting questions about the limits of vertical fragmentation. Electronics is the sector with the highest extent of vertical specialization among all industries. It is characterized by a high value to weight ratio and production of parts and components can easily be separated in time and space. The driving forces discussed are: technology that allows separation of activities in the supply chain in time and space; organizational innovations that take advantage of such new technologies; the role of services - notably the increasing service content of goods following expanding product diversity and customization to consumer demand - but also the rising demand for sophisticated logistics. It is indeed argued that services links make or break a supply chain. The paper argues that the proliferation of international production sharing requires a coherent policy response, particularly in developing countries, since a chain is as strong as its weakest link. It discusses the complementarities between trade liberalization in goods and services, investment policy, protection of intellectual property and competition policy, where it suggests that there may be a case for looking at the impact of lead firms buying power.
Keywords: 330; production sharing; automotive sector; electronics; services trade liberalization